Evolution of volcanic rifted margins: origin of seaward dipping reflectors with insights from flexure and 'process-oriented’ gravity modelling - Morgan, RL (2018)
Seaward dipping reflectors (SDRs) are ubiquitous features of the offshore regions of volcanic rifted continental margins where they comprise wedge-shaped packages of mainly extrusive lava flows. SDRs are typically observed on seismic reflection profiles; a compilation of which is studied in this thesis. A seismic reflection profile from offshore Greenland is re-processed in order to quantify the impact of semblance analysis on SDR geometry. With constraints on geometry known, this thesis presents a simple model in which SDRs are formed by a succession of dykes which intrude and load the crust. These loads cause a surface flexure, which is subsequently infilled and loaded by volcanic material. A flexural model explains the arcuate shape, limited offlap geometries and down-dip thickening of SDRs as observed in seismic reflection profile data. By comparing observed and calculated dips we are able to constrain the elastic plate model type and the effective elastic thickness of extended lithosphere, Te. Results suggest a broken plate or significantly weakened continuous plate model is required to produce the characteristic arcuate shape. Decreasing the Te for successive loads as rifting progresses produces offlap of sub-packages, while increasing the Te produces onlap. We have verified our results using process-oriented gravity modelling, in which the gravity effect of surface volcanic infill loads is calculated and combined with the gravity effect of buried dyke loads and the gravity effect of their isostatic compensation. Results from a case study interpreting a set of seismic reflection surveys from the Orange Basin, offshore Namibia show good general agreement between observed Airy isostatic anomalies and calculated gravity anomalies with Te in the range 1-3km. The steep gradient that is often observed in the Airy isostatic gravity anomaly at rifted margins is therefore a useful proxy for the seaward edge of the dykes that intrude the crust prior to seafloor spreading.